As paisagens rurais: do "determinismo natural" ao "determinismo político - Cavaco, Carminda (Finisterra, 2005)
Landscape is a recurring subject in the geographical literature and one which has been subject to analysis from a variety of different perspectives. Rural landscapes, in particular, usually account for a full chapter in most rural geography textbooks. Rural landscape is an ecological construction as well as an historical and cultural one, a heritage of the past as well as the result of new dynamics. While exhibiting great diversity, rural landscapes can nevertheless be divided into a number of main types. Many factors contribute to this diversity, from production objectives to land tenure regimes, inheritance regimes, productive structures, logics and strategies and the degree and characteristics of market participation. The focus of this paper is on agricultural and agritrade policies as engines of landscape transformation at the national, international and global levels. Rural policies are also considered in the case of some OECD countries and the European Union in particular. Finally, the foreseeable consequences of the Eastern enlargement of the EU upon the dynamics of creation and transformation of agrarian and rural landscapes is analysed, with special emphasis on the Portuguese case.